GAMBARAN BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEMATIAN NEONATAL (STUDI KASUS DI WILAYAH KERJA PUSKESMAS TASIKMADU KABUPATEN KARANGANYAR TAHUN 2015) - Oktavia Ayu Nur W.; Sri Winarni; Djoko Nugroho (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Many indicators used to measure mortality data, one of it is Neonatal Mortality Rate. Tasikmadu Health Centre is one of 21 health centers in Karanganyar with the highest Neonatal Mortality Rate of 17.19 per 1,000 live births in 2015. The purposes of this research are to analyze the relationship between antenatal care visits, history of maternal disease, exclusive breastfeeding and neonatal mortality in Tasikmadu Health Centre, Kayanganyar in 2015. The type of research is explanatory research with research design case control study. Population of cases are mothers who has a baby dies aged 0-28 days in 2015, there are about 11 deaths, and then were taken sample of the entire population. While population control is a mother who has a baby alive in 2015 as many as 814 then samples were taken in the ratio 1:2, it is about 22. Analysis of the data used is including univariate ang bivariate descriptive. The results of univariate analysis showed the largest percentage of respondents at risk of birth spacing (54.5%), there is no birth complications (87.9%), antenatal care visits according to the standard (54.5%), there is no history of disease (93.9%) and there is exclusive breastfeeding (63.6%). The results of the bivariate descriptive analysis showed mothers who had infants with neonatal deaths are more common in birth spacing risk (41.7%), there are birth complications (50%), ANC is not according to the standard (50%), history of disease (50%), the group is not exclusive breastfeeding (41.7%). It is suggested to staff of Tasikmadu health center to give socialization about childbirth healthy age and safe distance for a pregnancy to women of childbearing age when PKK encounter and in Posyandu is held in once a month